Incorporating the Ecological, Socio-economic and Institutional Conceptual Model Framework for Sustainable Management of Small-scale Mud Crab (Scylla serrata) Fishery in Western Seram Regency, Indonesia: 10.32526/ennrj/19/2020189 - Natan, Yuliana; Tetelepta, Johannes M.S.; Pattikawa, Jesaja A.; Ongkers, Ong T.S. (Environment and Natural Resources Journal, 2021)
Mud crab Scylla serrata of Kotania Bay and Pelita Jaya Bay of Western Seram District, has been harvested by local fishermen for more than 25 years. The mud crab has high economic value, and there is always a market for this fishery. The economic dependence of the fishermen forces them to harvest this resource extensively. No existing management strategy and extensive exploitation leads to unsustainable conditions of this fishery. With inadequate data condition, the Driver-Pressure-State-Impact-Response (DPSIR) model constructs an ecological, social-economy, and institutional conceptual model framework for sustainable management of this fishery. The driving force (D) in this fishery comes from the local fishers harvesting the mud crab. The two most sensitive attributes that affected mud crab sustainability from Rapfish analysis were used as state-level of DPSIR methodology. The result shows that the most sensitive variables from ecological, socio-economy, and institution were: caught before maturity, mud crab size, consumer attitude towards sustainability, just management, government quality, and monitoring and reporting, respectively. It was concluded that this conceptual model allows a better understanding of how the mud crab S. serrata system works and management actions taken at different system components. This conceptual model framework can be a useful tool to incorporate the participation of stakeholders, managers, and scientists in the process of a sustainable management plan.